PENGARUH KOMPENSASI, PENGEMBANGAN KARIR DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PT THAMRIN BROTHERS SENTRAL YAMAHA BENGKULU - Doni Saputra Simanjuntak; Janusi Waliamin; Sintia Safrianti (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2025)
The purpose study determine how much inflluence Compensatiion, Career Development and Communication on Employee Performance PT. Thamrin Brothers Sentral Yamaha Bengkulu. This research quantitative study. The research method explanatory approach research. study quantitative data. The data from distributing questionnaires employees PT. Thamrin Brothers Sentral Yamaha Bengkulu. population study all employees of PT. Thamrin Brothers Sentral Yamaha Bengkulu totaling 75 employees, analysis study used SPSS 25, data analysis method multiple linear regression, t-test f-test. Compensation significant effect employee performance PT. Thamrin Brothers Sentral Yamaha Bengkulu Career Development significant effect employee performance PT. Thamrin Brothers Sentral Yamaha Bengkulu, Communication significant effect employee performance PT. Thamrin Brothers Sentral Yamaha Bengkulu, Compensation Career Development Communication employee performance together a simultaneous effect.